CLINICAL PICTURE OF VEGETATIVE DYSTONIA IN PRE-CONSTRUCTION AGE ADOLESCENTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This work is devoted to studying the problem of vetetative disorders in children and adolescents, as well as its impact on physical and physiological indicators. This is important because they form the basis of the contingent for conscription. Information is analyzed by age and type of signs identified during the medical examination. A methodology for eliminating these diseases and ways to prevent recurrences are given.